Quantum defects by design - Bassett, Lee C.; Alkauskas, Audrius; Exarhos, Annemarie L.; Fu, Kai-Mei C. (Nanophotonics (Berlin, Germany), 2019)
Optically active point defects in wide-bandgap crystals are leading building blocks for quantum information technologies including quantum processors, repeaters, simulators, and sensors. Although defects and impurities are ubiquitous in all materials, select defect configurations in certain materials harbor coherent electronic and nuclear quantum states that can be optically and electronically addressed in solid-state devices, in some cases even at room temperature. Historically, the study of quantum point defects has been limited to a relatively small set of host materials and defect systems. In this article, we consider the potential for identifying defects in new materials, either to advance known applications in quantum science or to enable entirely new capabilities. We propose that, in principle, it should be possible to reverse the historical approach, which is partially based on accidental discovery, in order to quantum defects with desired properties suitable for specific applications. We discuss the biggest obstacles on the road towards this goal, in particular those related to theoretical prediction, materials growth and processing, and experimental characterization.